Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ese3.1173
|View full text |Cite
|
Sign up to set email alerts
|

Raising thermal efficiency of solar water‐pump using Oldroyd‐B nanofluids' flow: An optimal thermal application

Abstract: It is well known that solar energy is the main source of thermal energy coming from the sun responsible for huge operations in engineering studies. It can be seen in the technology of photovoltaic cells, solar streetlights, solar energy plates, and solar water pumping. This study is for investigating solar radiation as well as a method to improve the performance of the solar water pump (SWP) with the use of solar radiation along with nanotechnology. The thermal transfer performance of the pump is checked for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Entropy was recommended by Jamshed et al 24,77,78 to optimize thermal applications, while Shahzad et al 79 used it to growth the currenteffectiveness of a solar water pump used in NFs movement. References [80][81][82][83][84][85][86] did similar work.…”
Section: Pmentioning
confidence: 80%
“…Entropy was recommended by Jamshed et al 24,77,78 to optimize thermal applications, while Shahzad et al 79 used it to growth the currenteffectiveness of a solar water pump used in NFs movement. References [80][81][82][83][84][85][86] did similar work.…”
Section: Pmentioning
confidence: 80%
“…Parvin et al 23 presented the numerical conduct of 2D-Magneto double-diffusive convection flow of HNF over PMM. Faisal, et al 24 indicated the raising of heat effectiveness of solar water-pump utilizing HNFs over PMM. Banerjee and Paul 25 reviewed the most recent studies and development with the applications of PM combustion.…”
mentioning
confidence: 99%